26 The end of life: an overview of issues and a project to optimise care in Huntington's disease patients. Issue 12 (14th November 2022) - Roberts, Kris; Nielsen, Fiona; Dale, Maria; Kiani, Reza
Abstract : Objectives: This project aims to optimise End of Life (EOL) care at Mill Lodge, a specialist 14-bed neuropsychiatric ward in Leicestershire, UK. The service functions primarily for patients with Huntington's Disease (HD), a disorder that significantly reduces life expectancy and necessitates inpatient EoL care. After an initial stakeholder meeting, specific aims were identified: to establish the level of staff confidence in dealing with issues around EoL; identify specific areas of EoL care that staff felt could be improved; and to introduce a series of initiatives to optimise EoL care for our patients using a QI framework. Methods: The first stage of intervention included the planning and delivery of an educational event on EoL care specific to HD, achieved with our regional palliative care colleagues. As well as our inpatient nursing and medical staff and the palliative care teams, local GPs, district nursing colleagues, speech and language therapists and psychologists attended. The meeting allowed an open forum where we were able to identify barriers and facilitators to optimal care from all aspects of the assembled MDT. We also commenced involvement with the local QI team to develop the project. Results: Initial interactions revealed that staff confidence in dealing with EoL care was low. Issues with care-planning; medications; communication barriers; and when to refer for specialist help were key reasons for this. A range of interventions were commenced to enhance collaborative working between the teams overlapping in EoL care; the streamlining of medication prescription and administration; and to enhance communication between staff, patients and their carers. Conclusions: Staff without specialist knowledge require support. The efforts made to improve collaboration with external colleagues broke down barriers that were preventing optimal care and allowed all parties to express their opinions. This allowed us to transparently appraise our current processes and optimise guidance within this complex area. The journey of optimisation continues, with practical educational interventions planned, such as syringe-driver training, and efforts to improve shared documentation. Collaborative working between different disciplines continues, with, for example, psychology-led reflective debriefing. Liaison with external specialist HD teams is beginning. Optimal, collaborative EoL care from a confident team is possible and a crucial part of care for this unique patient group.